2009
DOI: 10.1007/s10482-009-9348-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and transmission of antimicrobial resistance among Aeromonas populations from a duckweed aquaculture based hospital sewage water recycling system in Bangladesh

Abstract: In order to investigate the influence of a duckweed aquaculture based hospital sewage water recycling plant on the prevalence and dissemination of antibiotic resistance, we made use of an existing collection of 1,315 Aeromonas isolates that were previously typed by the biochemical fingerprinting PhP-AE system. In these treatment plant, hospital raw sewage water is first collected in a settlement pond (referred to as sewage water in this study) and is then transferred to a lagoon, where the duckweed (Lemnaceae)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
1
8
0
2
Order By: Relevance
“…For example, an important part of sewage water purification in the future will be monitoring the influence of the process on the antimicrobial susceptibility profiles of bacterial indicators that could spread to the environment and to humans [33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an important part of sewage water purification in the future will be monitoring the influence of the process on the antimicrobial susceptibility profiles of bacterial indicators that could spread to the environment and to humans [33].…”
Section: Resultsmentioning
confidence: 99%
“…First, it is well documented that it allows antibiotic resistance determinants to spread from one species of bacteria to another [30 -32]. For example, there is good evidence for horizontal transfer of resistance genes between bacteria that cause infections in animals and those that cause infection in humans [33]. Second, resistance determinants for multiple antibiotics can potentially be transmitted at the same time.…”
Section: Antibiotic Resistant and Multiple-antibiotic Resistant Bacteriamentioning
confidence: 99%
“…This sort of transfer apparently occurs quite commonly within environmental reservoirs where resistance genes are generated by mutation, where bacteria and antimicrobial agents coexist, and where the bacterial population is high. There is strong evidence for horizontal transfer of resistance genes between bacteria that cause infections in animals and those that cause infection in humans [28]. It was reported that environmental isolates of MARB could transfer resistance to previously susceptible normal flora Escherichia coli [29].…”
Section: Emergence Of Multiple Antibiotic Resistant Bacteria (Marb)mentioning
confidence: 99%
“…Some new technologies that have potential for more efficient waste treatment are essential. Note that an important part of sewage water purification in the future will be monitoring the influence of the process on the antimicrobial susceptibility profiles of bacterial indicators that could spread to the environment and to humans [59].…”
Section: Antibiotics and Marb In The Environment: Possible Remediesmentioning
confidence: 99%